PENINGKATAN MANAJEMEN USAHA BERBASIS CREATIVE PACKAGING PADA UMKM “BAKPIA IVAN” DI DESA JANTEN, YOGYAKARTA - Astri Wulandari; Mutaqin Akbar; Rosalia Prismarini Nurdiarti (Jurnal Pengabdian UntukMu NegeRI, 2019)
“Bakpia Ivan", Small and Medium Business Unit is managed by family and hereditary manner, so that several times there are employee turnover and sometimes causes the production process to be slightly inhibited. Another thing that is a problem is the lack of awareness of the product packaging process (creative packaging) that is able to attract consumer interest and from the side of packaging security. This problem is linear unoptimal brand awareness and brand patent rights, so that when the product arrives at the reseller, the packaging is often replaced with other brands even though the contents are Bakpia Ivan. The purpose of this public service activity, first is to increase awareness of product packaging, positioning. Secondly, providing socialization and training about creative packaging, starting from the most basic capabilities. The method used in this activity is socialization and training. First, socializing and demonstrating how to begin packaging. Secondly, renew the logo design. Third, conduct social experiments related to logo renewal. The result of this activity is the acceptance of product packaging updates by the market so it can be expand sales and market segmentation. Second, the renewal of the logo / packaging design will be increasingly recognized and realized loyal consumers. Keywords: creative packaging, bakpia ivan, segmentation, positioning